Pengaruh Komunikasi terhadap Kinerja Aparatur Sipil Negara di Kantor Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Utara Masa Covid-19 - Ara Auza (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to determine the effect of Communication on the performance of the State Civil Apparatus during the Covid-19 pandemic at the Regional People's Representative Council Office of North Sumatra Province. This study uses the theory of Communication. This research was examined at the Regional People's Legislative Council Office of North Sumatra Province. The research method used in this research is correlational quantitative. The population in this study is the State Civil Apparatus (ASN) in the Regional People's Representative Council Office of North Sumatra Province, totaling 106 people. The results of this study indicate that: (1) There is an influence of State Civil Apparatus Communication on the performance of State Civil Apparatuses in the Regional House of Representatives of North Sumatra Province of 0.383. The level of correlation is low but sure between the communication variables of the State Civil Apparatus and the Performance of the State Civil Apparatus during the Covid-19 period in the Regional People's Representative Council of North Sumatra Province.